2021
DOI: 10.1016/j.ijid.2021.07.064
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of SARS-CoV-2 relapse with remdesivir and neutralizing antibodies cocktail in a patient with X-linked agammaglobulinaemia

Abstract: During the Coronavirus Disease 2019 pandemic, patients with humoral immunodeficiency are at higher risk of developing chronic infection and having negative outcome. Little data are available on therapeutic options for this population. We discuss the treatment of SARS-CoV-2 relapse with remdesivir and monoclonal antibodies in an adult patient with X-Linked Agammaglobulinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Of note, 4 patients with XLA showed longer durations of testing positive for SARS-CoV-2 (30 to 64 days), and 4 additional cases had reports of rehospitalization or of testing positive, then negative, then positive again. As most people with XLA have no or very few B cells and thus produce no or few antibodies, this finding supports the importance of antibodies in clearing SARS-CoV-2 [ 20 , 24 , 33 , 35 , 49 , 55 , 58 ]]. No case reports included information on whole viral genome sequencing for SARS-CoV-2 to allow for evaluation of the impact of PI on the emergence of variants of concern.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Of note, 4 patients with XLA showed longer durations of testing positive for SARS-CoV-2 (30 to 64 days), and 4 additional cases had reports of rehospitalization or of testing positive, then negative, then positive again. As most people with XLA have no or very few B cells and thus produce no or few antibodies, this finding supports the importance of antibodies in clearing SARS-CoV-2 [ 20 , 24 , 33 , 35 , 49 , 55 , 58 ]]. No case reports included information on whole viral genome sequencing for SARS-CoV-2 to allow for evaluation of the impact of PI on the emergence of variants of concern.…”
Section: Resultssupporting
confidence: 59%
“…A total of 459 people with PI and COVID-19 are described from 54 of the 68 studies [ 12 , 13 , 16 , [18] , [19] , [20] , [21] , 24 , 26 , 27 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ] (Table 2). These cases came from case reports as well as cohort studies with information available for individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, data on effects of COVID-19 treatments in IEI patients have been described ( 14 16 ). Recently, our group demonstrated that, during the second year of the pandemic, mabs administration had a beneficial effect on the likelihood of hospitalization and development of severe disease confirming previous data observed in a lower number of patients ( 17 , 18 ). Poor data in IEI are available regarding antiviral therapy, except for some case reports describing remdesivir as effective for viral clearance in XLA patients and in severely immunocompromised patients ( 19 , 20 ).…”
Section: Introductionsupporting
confidence: 86%
“…It is unknown, whether a lack of specific humoral immunity to SARS-CoV-2 per se leads to an increased risk of RNAemia. Based on numerous mild COVID-19 cases in XLA patients (2,(15)(16)(17)(18)(19)(20), at least generally persisting and high viral loads seem unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to humoral immunity, early clinical data from XLA patients suggested that lack of SARS-CoV-2 humoral immunity may be sufficiently compensated by innate and T cell immunity in order to prevent severe COVID-19 (2,(15)(16)(17)(18)(19)(20). On the other hand, patients with Good's syndrome, a thymoma-associated hypogammaglobulinemia with B and/or T cell deficiency and lack of specific humoral immune response, were reported to be at significantly increased risk for severe COVID-19 and a high case fatality rate (12).…”
Section: Introductionmentioning
confidence: 99%